NEW MEDIA IMPACT ON CONSUMER PERCEPTION OF ASPIRATIONAL BEAUTY ADVERTISEMENT - Soni, Twinkle; Vinod; Dhaliwal, Sunny; Verma, Amit (ShodhKosh: Journal of Visual and Performing Arts, 2025)
The high rate of development of new media platforms has changed the situation in the world of aspirational beauty advertising, and it greatly affects the perceptions of consumers regarding the beauty ideal. This paper discusses the development of digital spaces (specifically social media apps like Instagram, Tik Tok, and YouTube) and how they redefine the processes through which people perceive, internalize, or react to depictions of aspiration beauty. The new media, in contrast to the old, encourages participation in the form of user-created content, influencer marketing, and algorithms and recommendations that push certain trends of beauty to the forefront. The study explores how these dynamics can cause changes in the consumer perceptions of authenticity, realism, and attainability in beauty ideals. The study is based on the main theoretical themes, such as the social comparison theory, cultivation theory, and self-discrepancy theory, which examine the psychological consequences of being inundated with digitally mediated ideals of beauty. A mixed-method survey, interviews, and content analysis methodology are used to ensure that both quantitative trends as well as qualitative information are obtained. The results show that new media enhances the self-comparison behavior, dissolves the line between the aspirational and attainable beauty, and creates a new definition of authenticity with a curated brand identity.